Development of Number Card Media in Mathematics Learning for Elementary School Students - Jannah, Askhabul; Irwandi; Lubis, Azmil Hasan; Julia, Nora Maulida (MANDAILING GLOBAL EDUKASIA, 2024)
Learning media is one of the important aspects in a learning process. Learning media can facilitate the achievement of learning objectives. This study aims to develop mathematics learning media in the form of number cards. This research is a research and development. The development model used is ADDIE. The subjects of this study were media experts, material experts, class teachers and students. Data were collected using a questionnaire technique. The data obtained were then analyzed using descriptive statistical techniques. The results of the study showed that the number card media was declared feasible and practical for use in elementary school mathematics learning. This is evidenced by the results of the feasibility test conducted by media experts and material experts, each of which obtained the category